Author Misrepresentation of Institutional Affiliations: Protocol for an Exploratory Case Study - Navarrete-Couble, M; Bachelet-Norelli, V; Lizana-Montecinos, F; Uribe, F; Meza-Ducaud, N (BMJ Publishing Group, 2019)
Introduction University ranking systems and the publish-or-perish dictum, among other factors, are driving universities and researchers around the world to increase their research productivity. Authors frequently report multiple affiliations in published articles. It is not known if the reported institutional affiliations are real affiliations, which is when the universities have contributed substantially to the research conducted and to the published manuscript. This study aims to establish whether there is an empirical basis for author affiliation misrepresentation in authors with multiple institutional affiliations. Methods and analysis This individual secondary data exploratory analysis on Scopus-indexed articles for 2016 will search all authors who report multiple institutional affiliations in which at least one of the affiliations is to a Chilean university. We will consider that misrepresentation of an affiliation is more likely when it is not possible to verify objectively a link between the author and the mentioned institution through institutional websites. If we cannot corroborate the author affiliation, we will consider this a finding of potential misrepresentation of the affiliation. We will summarise results with descriptive statistics. Ethics and dissemination The study protocol was approved by the institutional ethics committee of Universidad de Santiago de Chile, Resolution No. 261, and dated January 15, 2018. Results will be submitted to the World Conference on Research Integrity, among other meetings on publication ethics and research integrity, and will be published in scientific, peer-reviewed journals. © Author(s) (or their employer(s)) 2019. Re-use permitted under CC BY-NC. No commercial re-use. See rights and permissions. Published by BMJ.